Challenges and strategic approaches in EFL students’ prose analysis essays - Setyowati, Lestari; Benyamin, Bianda Alzena; Karmina, Sari; MR, Elvira Rosyida; Sukmawan, Sony (JOALL (Journal of Applied Linguistics and Literature), 2025)
This study investigates the difficulties experienced by EFL students in writing essays for prose analysis, along with the strategies they use to overcome these challenges. This research used qualitative research with a case study design. The participants of the study were 14 students of the English Language and Literature department from one of the state universities in Malang, East Java. The data collection took two months. The instruments used were interviews, questionaires, observation, and documentation. The result shows that students face major challenges in essay writing, particularly in content and organization, such as making good thesis statements and conclusions, and moderate difficulties with grammar. However, they demonstrated sufficient vocabulary and mechanical skills. To address these issues, students reported employing different types of strategies. The most common were mind mapping, continuous practice, and peer discussions. Moderately used strategies included seeking feedback, using audiovisual resources, and consulting dictionaries. The least used were translating, watching YouTube videos, and using AI tools or application. These strategies were applied throughout the writing process—pre-writing, whilst writing, and post-writing—and students found them effective in improving their prose analysis essays.